Sistem Penghantaran Obat Mutakhir: Tantangan Formulasi Nano untuk Fitokimia yang Sulit Larut dalam Air - Juliana Palungan; Rona Hawa Kamilah; Moh. Firmansah; Sima Asmara Dewa Marya Mahardika Putri; Winda Wahyu Setya Rahmah; M Iman Tarmizi Thaher (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The poor water solubility and low oral bioavailability of various phytochemical compounds (BCS Classes II and IV) continue to be major obstacles in the development of modern therapeutics, despite their remarkable therapeutic potential. This narrative review critically evaluates the use of nanoscale drug delivery systems to overcome the biopharmaceutical limitations of hydrophobic phytochemicals and pinpoints key challenges in clinical translation and industrial-scale production. The review provides a comprehensive analysis of the latest literature on the effectiveness of nanotechnology-based physicochemical modifications, including solid lipid nanoparticles (SLNs), nanostructured lipid carriers (NLCs), nanosuspensions, polymeric micelles, liposomes, and phytosomes. The review's results indicate that nano-carrier engineering significantly enhances solubility, avoids first-pass metabolic degradation, and enables targeted delivery. Specifically, nanoformulations have proven effective at penetrating the dense matrix of the tumor microenvironment (TME) in cancer therapy, crossing the blood-brain barrier (BBB) in neurodegenerative diseases, and protecting drugs from stomach acid in infectious and metabolic conditions. However, the transition toward commercialization is hindered by issues of long-term physicochemical stability (e.g., lipid polymorphic transitions) and challenges in standardizing botanical raw materials. These issues affect the reproducibility of large-scale production, ultimately delaying the availability of these promising therapies to patients in need. In conclusion, while nanoformulations offer transformative solutions for overcoming phytochemical biological barriers, standardizing protocols, innovating green synthesis, and fostering interdisciplinary collaboration are essential for overcoming scalability barriers and preparing these innovations for clinical application.